ASESMEN PERKEMBANGAN ANAK USIA DINI - andini dwi arumsari; Vina Mayangsari Putri (MOTORIC, 2020)
Assessment is a process to find out a person's ability, to a competency, based on the evidence. Basically, it is a process of searching for evidence. Meanwhile, development is a process that occurs in every human being. In this period, human development is closely related to the level of maturity. Changes made progressively and systematically in humans. Then the younger children have more than 6 years of age. Where children are still experiencing a lot of development. Assessment conducted on AUD to support the development of children since AUD, so that parents and teachers are able to provide appropriate stimulus and intervention to children Keywords: educational games, memorizing, numbers 1-20